Fair exotics : xenophobic subjects in English literature, 1720-1850 - Sudan, Rajani (Philadelphia : University of Pennsylvania Press, 2002)
"An original and elegant work that will make signal contributions to the fields of eighteenth-century studies and Romanticism, and to the study of British nationalism and colonialism."--Adela Pinch, University of Michigan.
Frontmatter -- Contents -- Introduction -- 1. Institutionalizing Xenophobia: Johnson's Project -- 2. De Quincey and the Topography of Romantic Desire -- 3. Mothered Identities: Facing the Nation in the Works of Mary Wollstonecraft -- 4. Fair Exotics: Two Case Histories in Frankenstein and Villette -- Afterword -- Notes -- Works Cited -- Index -- Acknowledgments.
Series statement on jacket.
Includes bibliographical references (pages 181-188) and index.
In English.
JSTOR
Keywords: English literature -- 18th century -- History and criticism; Exoticism in literature; English literature -- 19th century -- History and criticism; Xenophobia -- Great Britain -- History -- 18th century; Xenophobia -- Great Britain -- History -- 19th century; Foreign countries in literature; Noncitizens in literature; Littérature anglaise -- 18e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Xénophobie -- Grande-Bretagne -- Histoire -- 18e siècle.; Xénophobie -- Grande-Bretagne -- Histoire -- 19e siècle.; Pays étrangers dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Noncitizens in literature; English literature; Exoticism in literature; Foreign countries in literature; Xenophobia; Great Britain; Noncitizens; 1700-1899; Cultural Studies; Literature; Literary criticism; Criticism, interpretation, etc; History; Literary criticism; Critiques littéraires.